Economic Development Models of Doha and Dubai: A Comparative Analysis - Aldana Jassim Althani (15445412) (2023)
This chapter explores the development models of Doha and Dubai by highlighting the economic, political, and social factors in Qatar and Dubai. This research examines the historical context of Dubai and Qatar and digs deeper to explore how each state adopted a certain development path, and then the role of leadership in promoting the development through states’ strategic visions. This chapter reports that profound political, economic, and social factors lead to different development strategies for Dubai and Doha. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_26